Obstetric anesthesia. - Chang Hun, Roberto (2015)
Every obstetric anesthesia involves the safety of two individuals: a mother and child; with their potential danger of hypoxia, increasingly it required for childbirth or its complications more frequently, often for patients without pre-anesthetic controls, even after a recent meal, which increases the incidence of accidents that sometimes end with life of the patient.